Annular Pancreas in infancy - Ery Suhaymi; Djeni Bijantoro (ANATOMICA MEDICAL JOURNAL | AMJ, 2022)
Abstract: Annular pancreas is a rare congenital disorder where the symptoms that appear in this patient are symptoms of obstruction caused by the presence of pancreatic tissue that forms a ring around the descending part of the duodenum. The annular pancreas has a ratio of 1:20,000 births that may show stenotic or obstructive symptoms early in life. With a plain abdominal radiograph taken in the erect position, a “double bubble” appearance is seen, which is typical of the annular pancreas. In this case, A boy 10 month, with chief complaint vomiting, with containt vomiting every time he eat (breast milk). It had been suffered since he was born. Patient was born by midwife, aterm. Since he born, patient used took antivomitus from pediatric. Patient has been documented by barium meal to hospitalization, and was differential diagnosed with obstruction partial duodenum; duodenal web; pyloric stenosis; annulare pancreas with right scrotalis hernia. In these patient the treatment with perform Duodeno-Jejunustomy.Keywords: Annular pancreas, double bubble, Duodeno-Jejunustomy